Enhancement the Thermal Stability and the Mechanical Properties of Acrylonitrile-Butadiene Copolymer by Grafting Antioxidant - Abdulaziz Ibrahim Al-Ghonamy; A. A. El-Wakil; M. Ramadan (International Journal of Polymer Science)
Monomeric antioxidants are widely used as effective antioxidants to protect polymers against thermal oxidation. Low molecular weight antioxidants are easily lost from polymer through migration, evaporation, and extraction. Physical loss of antioxidants is considered to be major concern in the environmental issues and safety regulation as well as long life time of polymers. The grafting copolymerization of natural rubber and o-aminophenol was carried out by using two-roll mill machine. The prepared natural rubber-graft-o-Aminophenol, NR-graft-o-AP, was analysed by using Infrared and 1H-NMR Spectroscopy techniques. The thermal stability, mechanical properties, and ultrasonic attenuation coefficient were evaluated for NBR vulcanizates containing the commercial antioxidant, N-phenyl-𝛽-naphthylamine (PBN), the prepared grafted antioxidant, NR-graft-o-AP, and the control vulcanizate. Results of the thermal stability showed that the prepared NR-graft-o-AP can protect NBR vulcanizate against thermal treatment much better than the commercial antioxidant, PBN, and control mix, respectively. The prepared grafted antioxidant improves the mechanical properties of NBR vulcanizate.